Corrosion of glass, ceramics, and ceramic superconductors principles, testing, characterization and applications - Clark, David E.; Zoitos, Bruce K. (Noyes, 1992)
Presents fundamental chemical reactions, equations, computer codes and models, and examples by professionals in the field. Contents: Biomaterials, Optical Components, Construction, Materials, Nuclear Waste Containment, Ceramic, Superconductors, and Archeologically Significant Articles.
Keywords: Ceramic materials -- Corrosion.; Glass -- Corrosion.; Ceramic superconductors -- Corrosion.; elektronické knihy; electronic books